Comparison of epifluorescence microscopy and flow cytometry in counting freshwater picophytoplankton - Salmi, Pauliina; Mäki, Anita; Mikkonen, Anu; Pupponen, Veli-Mikko; Vuorio, Kristiina; Tiirola, Marja (Suomen ympäristökeskus, 2021)
The smaller the phytoplankton, the greater effort is required to distinguish individual cells by optics-based methods. Flow cytometry is widely applied in marine picophytoplankton research, but in freshwater research its role has remained minor. We compared epifluorescence microscopy and flow cytometry in assessing the composition, abundance and cell sizes of autofluorescent picophytoplankton in epilimnia of 46 Finnish lakes. Phycocyaninrich picocyanobacteria were the most dominant. The two methods yielded comparable total picophytoplankton abundances, but the determination of cell sizes, and thus total biomasses, were on average an order of magnitude higher in the microscopy results. However, flow cytometry yielded higher cell sizes when applied on small-celled cultured algae. Our study demonstrated that both epifluorescence microscopy and flow cytometry are useful methods in assessing abundances of phycocyanin-rich and phycoerythrin-rich picocyanobacteria and eukaryotic picophytoplankton in lakes. However, accurate determination of cell size and biomass remain challenges for microscopy and especially for flow cytometry.